Development of technology of pulverized coal injection in Ukraine’s blast furnaces in variable liquid and gas dynamic conditions - Semenov, Yu.S.; Shumelchyk, Ie.I.; Horupakha, V.V. (Фундаментальные и прикладные проблемы черной металлургии, 2018)
The aim of the work is to study the features of the use of pulverized coal (PCI) in the conditions of the blast furnace (BF) No. 5 of Metinvest Holding Ltd (Ukraine). Целью работы является изучение особенностей использования пылеугольного топлива (ПУТ) в условиях доменной печи (ДП) № 5 компании "Метинвест Холдинг Лтд" (Украина). Метою роботи є вивчення особливостей використання пиловугільного палива (ПВП) в умовах доменної печі (ДП) № 5 компанії "Метінвест Холдинг Лтд" (Україна).